Tetrahedral chalcopyrite quantum dots in solar-cell applications - Ojajärvi, Juho (2010)
We have considered two different chalcopyrite material combinations suggested for intermediate-band solar cell (IBSC) sample fabrication in Helmholtz Zentrum, Berlin. We have obtained the maximum theoretical efficiency values of these two chalcopyrite IBSCs. The optimal sizes of the chalcopyrite quantum dots (QDs) in the corresponding QD-IBSC implementations have been calculated. Optical absorption spectrum of a single chalcopyrite QD has been obtained for both systems. The effect of the QD geometry, especially the effect of the roundness of the QD, was examined. We hope that these results will help in the quest towards more efficient and more affordable solar cells.